Efficacy evaluation of albumin-bound paclitaxel combined with carboplatin as neoadjuvant chemotherapy for primary epithelial ovarian cancer - Huan Wang; Lingyun Fan; Xia Wu; Yimin Han (BMC, 2022)
Abstract Objective This study aimed to compare the efficacy of albumin-bound paclitaxel combined with carboplatin (Nab-TC) with that of traditional solvent-based paclitaxel combined with carboplatin (TC) as neoadjuvant chemotherapy (NAC) regimens for primary epithelial ovarian cancer. Methods Eighty patients with advanced primary epithelial ovarian cancer admitted for treatment at the Harbin Medical University Cancer Hospital from January 2015 to January 2020 were retrospectively selected. All patients underwent surgery after 1-4 courses of NAC with Nab-TC or TC regimen. Among the patients included for study, 40 patients in each group. Results The ORR in Nab-TC group was better compared to TC group (45% vs 40%), but the difference was not significant (P = 0.651). While the reduction rate of CA-125 value in the Nab-TC group was significantly better (P < 0.05). The postoperative complication rate such as postoperative blood transfusion (5% vs 35%) and postoperative infusion of human albumin (25% vs 55%) were significantly lower relative to the TC group. The median progression-free survival of the Nab-TC group was significantly longer relative to the TC group (20 months vs 13 months, P = 0.012), and the patient's quality of life was also better in the Nab-TC group (P < 0.05). Our study demonstrated that Nab-TC regimen and R0 represented the independent prognostic factors. Conclusion The efficacy of the Nab-TC regimen as NAC for advanced primary epithelial ovarian cancer was non-inferior to that of the TC regimen along with a lower incidence of adverse reactions, a longer PFS and a higher quality of life, supporting its therapeutic value in the clinic.